The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/term.220
|View full text |Cite
|
Sign up to set email alerts
|

Donor-matched comparison of dental pulp stem cells and bone marrow-derived mesenchymal stem cells in a rat model

Abstract: Dental pulp stem cells (DPSC) have drawn much interest for the regeneration of mineralized tissues, and several studies have compared DPSC to bone marrow-derived mesenchymal stem cells (BMMSC). However, conflicting results, possibly due to donor-associated variability, have been published and the regenerative potential of DPSC is currently unclear. In the present study we have sought to address this problem using a donor-matched experimental design to robustly compare the biological properties of DPSC and BMMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
152
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(167 citation statements)
references
References 32 publications
9
152
0
4
Order By: Relevance
“…DPSCs have the potential to differentiate into several lineages including osteogenic, adipocyte, muscle, neurons and cartilage (Gronthos et al 2000;Lee et al 2013;Nakatsuka et al 2010;Arthur et al 2008). Comparison of their multipotency with bone marrow stem cells (BMSCs), has demonstrated that proliferation, availability, and cell number of DPSCs were more elevated than for bone marrow MSCs (Huang et al 2009;Alge et al 2010). Moreover, DPSCs can easily be isolated from human pulp tissue and do not cause ethical and technical problems (Rodríguez-Lozano et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DPSCs have the potential to differentiate into several lineages including osteogenic, adipocyte, muscle, neurons and cartilage (Gronthos et al 2000;Lee et al 2013;Nakatsuka et al 2010;Arthur et al 2008). Comparison of their multipotency with bone marrow stem cells (BMSCs), has demonstrated that proliferation, availability, and cell number of DPSCs were more elevated than for bone marrow MSCs (Huang et al 2009;Alge et al 2010). Moreover, DPSCs can easily be isolated from human pulp tissue and do not cause ethical and technical problems (Rodríguez-Lozano et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Human dental pulp stromal cells (hDPSCs) were characterized as stem cells in 2000 (Alge et al 2010;Gronthos et al 2000). Thereafter, a number of studies confirmed that these cells are multi-potential and have the capacity to differentiate into progenitors which can 7 form bone, cartilage, adipose tissues, and so on (Laino et al 2005;Min et al 2008;Nakashima et al 2009;Zhang et al 2008).In recent years, it has been reported that mechanical loading could promote hDPSCs osteogenic differentiation and produce bone like tissue (Kraft et al 2010;Kraft et al 2011;Yu et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…DPSCs can differentiate into different kinds of cells and tissues [4], especially bone-like tissue, and their multipotency has been compared to those of Bone Marrow Stem Cells (BMSCs). It has been demonstrated that proliferation, availability, and cell number of DPSCs are greater than BMSCs [5]. DPSC has also been used to regenerate nerves [6], cornea [7], bladder and renal tissues [8], skeletal muscles [9], lung tissue [10] and has demonstrated good angiogenic [11] and neurogenic potential.…”
Section: Clinical Backgroundmentioning
confidence: 99%